Chitosan oligosaccharide/alginate nanoparticles as an effective carrier for astaxanthin with improving stability, in vitro oral bioaccessibility, and bioavailability. (March 2022) - Sorasitthiyanukarn, Feuangthit Niyamissara; Muangnoi, Chawanphat; Rojsitthisak, Pornchai; Rojsitthisak, Pranee
Abstract: Astaxanthin (ATX), a hydrophobic xanthophyll family of carotenoids, has various advantageous biological activities. Its use as a bioactive compound in functional foods, nutraceuticals, and dietary supplements is currently limited by its extremely low water solubility, poor bioaccessibility, and low bioavailability. To overcome these limitations, ATX-loaded chitosan oligosaccharide/alginate nanoparticles (ATX-COANPs) were fabricated by oil-in-water emulsification followed by ionotropic gelation, and conditions were optimized using the response surface methodology. Characteristics of optimal ATX-COANPs in terms of particle size, zeta potential, encapsulation efficiency, and loading capacity were 264 ± 32 nm, −22.1 ± 1.3 mV, 71.3 ± 2.2%, and 6.9 ± 1.6%, respectively. On transmission electron microscopy, ATX-COANPs have a spherical shape with a smooth surface and even size distribution. ATX-COANPs demonstrated good stability during storage and exposure to UV light, heat, acidic–alkaline, oxidation, and simulated gastrointestinal (GI) fluid conditions. In vitro release studies in simulated GI fluids demonstrated that ATX was released from ATX-COANPs in a sustained manner with Fickian diffusion mechanism. The in vitro bioaccessibility, bioavailability, and antioxidant activity of ATX were increased after encapsulating within COANPs. These findings suggest that ATX-COANPs have potential applications in developing an effective oral delivery system of ATX in nutraceuticals or functional foods. Graphical abstract: Image 1 Highlights: COANPs were successfully fabricated for encapsulating ATX. Encapsulation of ATX in COANPs enhanced its bioaccessibility during simulated digestion. Encapsulation of ATX in COANPs enhanced its antioxidant activity. The ATX-COANPs performed good stability during storage and under UV light. Encapsulation of ATX in COANPs enhanced its stability during simulated digestion.